UJI EFEK ANTIGLAUKOMA INFUS DAUN KITOLOD (Isotoma longiflora (L) C.Presl) TERHADAP TIKUS PUTIH JANTAN BERDASARKAN TEKANAN BOLA MATA - siska siska; hadi sunaryo; teja kusuma wardani (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
Glaucoma is abnormality in the eyes of the increasing pressure (intraocular) that able to push optic nerve so that can cause nerve optic damage in the eyes. The damage to the optic nerve can cause visual field reduction, so that can cause blindness. Increased intraocular pressure caused by inhibition of aqueous humeous. The mechanism of medication for glaucoma is to reduce intraocular pressure. Kitolod leaves (Isotoma longiflora (L) C.Presl.) One of the many wild plants used to treat eyes diseases in traditional societies, one to treat glaucoma, therefore to prove activities as antiglaucoma then do research in order to determine the effect infuse of kitolod leaf to the intraocular pressure. This research uses 5 groups negative, positive, concentration 40%, concentration 50%, concentration 60%. This research use the inducer prednisolone acetate eye drops 1% and the positive comparator is pilocarpine 2% eye drops. Measurement of eyes pressure use the tonometer Schiotz The results of the research showed that concentration 60% has effects of lowering the eye pressure is comparable with pilocarpine 2% eye drop.